Construction practice - Cooke, B. (Brian) (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2011)
'Construction is a highly practical subject. Students on all built environment degree programmes are expected to know and understand building technology from both a theoretical and practical standpoint. Construction site visits are a popular way for students to become acquainted with the practical aspects of construction, but these visits can only show students a small proportion of the technology of construction. Based around a series of full colour photographic sequences, augmented by carefully chosen line illustrations and text, Construction Practice provides students with a comprehensive overview of practical construction technology. The sequences follow a logical progression through the subject and include contemporary and established practice, as well as modern methods of construction. The book also includes some examples of continental European construction methods where these differ from established UK practice'--
'Construction is a highly practical subject. Students on all built environment degree programmes are expected to know and understand building technology from both a theoretical and practical standpoint. Construction site visits are a popular way for students to become acquainted with the practical aspects of construction, but these visits can only show students a small proportion of the technology of construction. Based around a series of full colour photographic sequences, augmented by carefully chosen line illustrations and text, Construction Practice provides students with a comprehensive overview of practical construction technology. The sequences follow a logical progression through the subject and include contemporary and established practice, as well as modern methods of construction. The book also includes some examples of continental European construction methods where these differ from established UK practice'--
Includes bibliographical references.
Keywords: Building; TECHNOLOGY & ENGINEERING / Construction / General